The Influence of Employee Emotion Fluctuation on Service Performance: An Experience Sampling Data Analysis - Zhang, Biqian; Zhao, Lei; Liu, Xiaoyan; Bu, Yinwei; Ren, Yingwei (Frontiers in Psychology, 2022)
Research on the relationship between emotions and job performance is ubiquitous, yet few scholars have examined the combined effects of different emotions. Drawing on the broaden-and-build theory and conservation of resources theory, we propose that employees’ daily emotion fluctuations (positive emotions vs. negative emotions) will affect their service performance in opposite directions. Furthermore, we propose these effects will be moderated by psychological (i.e., regulatory emotional self-efficacy; RESE) and physiological (i.e., sleep quality) characteristics of the employees. Based on the experience sampling method, data (N = 810) obtained from 187 frontline employees of 35 bank branches over 18 consecutive days supports our hypotheses.